Mediterranean Fever Gene Mutations and Messenger Ribonucleic Acid Expressions in Pediatric Patients With Familial Mediterranean Fever in the Trakya Region of Turkey - Hilmi TOZKIR,; Hakan GÜRKAN,; Neşe ÖZKAYIN,; Necdet SÜT3, (Archives of Rheumatology, 2014)
Objectives: This study aims to investigate the possible relationship between Mediterranean fever (MEFV) gene mutations and messenger ribonucleic acid (mRNA) expressions and to identify the link between phenotype and genotype of pediatric patients with Familial Mediterranean fever (FMF). Patients and methods: Seventy-one pediatric FMF patients who were identified with FMF symptoms and diagnosed with FMF according to Tel Hashomer criteria were included at Trakya University, Faculty of Medicine, Department of Paediatric Nephrology. The control group consisted of 73 healthy pediatric participants. Genomic deoxyribonucleic acid was isolated from whole blood samples and the following mutations of MFEV gene were analyzed: E148Q, P369S, H478Y, H479L, S675N, G678E, M680L, M680I (G>A and G>C), T681I, I692del, M694V, M694L, M694I, M695R, M695M, R717S, I720M, V722M, V726A, A744S and R761H. Total RNA isolation from leukocytes was performed and MEFV mRNA expression levels of the patients were compared by using real-time quantitative polymerase chain reaction method. β2 microglobulin was selected as the control gene. The comparison of mRNA expression levels among the patients was performed using the ΔCT method. Results: The most common clinical findings were abdominal pain, fever and vomiting. The mutation detection rate in the patient group was OR=4.1 (95% CI: 1.8-9.0) times higher than that of the control group. The MEFV mRNA expression level of the patients with MEFV gene mutations was lower compared to the control group, indicating statistical significance. Conclusion: Our study results support the findings of previous studies indicating that the MEFV mRNA expression levels of pediatric FMF patients with MEFV gene mutation are lower than the MEFV mRNA expression levels of healthy controls.